PRELIMINARY PHYTOCHEMICAL SCREENING AND IN VITRO ANTI-MICROBIAL ACTIVITY OF ETHANOLIC EXTRACTS OF SEEDS OF PUNICA GRANATUM AGAINST STANDARD PATHOGENIC STRAINS - Bora, Aditya Jyoti; Dash, Biswajit; Paul, Sujata; Gupta, Bikash (International Journal of Current Pharmaceutical Research, 2018)
Objective: To estimate the anti-microbial activity of ethanolic extract of Punica granatum seeds (family-Punicaceae) in association with phytochemical analysis. Methods: The ethanolic extract of the seeds of Punica granatum was prepared and investigate for phytochemical constituents using standard methods. Antimicrobial activities of ethanolic extract were carried out against one Gram positive bacteria (Staphylococcus aureus) and one Gram negative bacteria (Escherichia coli). The anti-fungal activity of the plant extract was evaluated on Candida albicans. The testing was done by the disc diffusion method. A zone of inhibition of ethanolic extract was compared with that of standard Tetracycline for anti-bacterial activities and Fluconazole for anti-fungal activity. Results: The result of this study showed a good antibacterial effect of pomegranate juice against both Gram negative and Gram positive bacteria. The antimicrobial activity of the fruit may be due to its high content of polyphenols which causes phenolic toxicity by interfering with the sulfhydryl group of the bacterial proteins and high content of tannins which interferes with bacterial membrane stability. Conclusion: The present study concluded that ethanolic extract of the seeds of Punica granatum contains the high existence of phytochemicals. The ethanolic extract of the plant was found to possess promising antimicrobial activity when compared with the standards.